An examination of the factorial structure of the Norwegian version of the sport anxiety scale - Abrahamsen, F. E.; Roberts, G. C.; Pensgaard, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The purpose of the present research was to develop and validate a Norwegian version of the sport anxiety scale (SAS-N), a multidimensional sport performance trait anxiety inventory. The SAS consists of three unique dimensions measuring somatic anxiety, worry and concentration disruption, respectively. The translation-back translation method was used in development of the SAS-N, and athletes from different sports in Norway (N=282) participated in the study. The findings are similar to those of the English original, and lend support for the use of this instrument with Norwegian athlete subjects.